Wollstonecraft, Mill, and Women's Human Rights - Botting, Eileen Hunt (Yale University Press, 2021)
This book argues that Mary Wollstonecraft and John Stuart Mill are the two primary architects of the modern theory of women’s rights as human rights. It only through addressing women’s rights, Botting argues, that the idea of human rights was given universal scope and application. Botting describes the development of the idea of women’s human rights beginning with the work of Wollstonecraft and Mill, and gives an account of their reception in both western and nonwestern contexts. Her goal is to strip liberal feminism of its Eurocentric bias and offer the theory that remains as a resource for thinking about women’s human rights globally.